Affect of Alcohol Consumption on the Academic Performance of Economics Students at an Institution of Higher Studies - De Dios Velázquez, Sergio; López Rodríguez, William Baldemar; González Ortiz, Charly (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2024)
OBJECTIVE: Determine the impact of alcohol consumption on the academic performance of Economics students. MATERIAL AND METHOD: The research design is descriptive and cross-sectional. The population under study comprises a sample of 50 students enrolled in the bachelor’s degree in economics of the Academic Division of Economic-Administrative Sciences. Likewise, for the collection of information, a questionnaire was applied. RESULTS: The consumption of alcoholic beverages did not represent a problem for the Economics students, nor for their academic performance, since the level of consumption was low and the high consumption is during vacation periods, not presenting a risk for them. Furthermore, they know the consequences and risks of consuming alcohol and most of them have considered quitting. CONCLUSIONS: The consumption of alcoholic beverages by Economics students is low, they even responded to consume only during vacation periods. Furthermore, they attend their classes, complete their homework, and there is no risk in their relationship with teachers or classmates, that is, as long as they control their consumption levels, there is no impact on their academic performance.